Kingdee in 2011 : stranding or dormancy - McFarlan, F. Warren (SAGE knowledge. Cases., 2016)
On February 2, 2012, Kingdee International announced that Richard Feng had resigned as Kingdee's executive director and president and CEO of Kingdee Software (China) Company Ltd., a wholly-owned subsidiary of Kingdee, due to family committments and other personal reasons, and would now be appointed as strategy consultant. At that time, Richard had served as Kingdee's president for one year. This case study examines this topic.